If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5z + -1) + -5(z + 2) = 11(z + 1) Reorder the terms: 6(-1 + 5z) + -5(z + 2) = 11(z + 1) (-1 * 6 + 5z * 6) + -5(z + 2) = 11(z + 1) (-6 + 30z) + -5(z + 2) = 11(z + 1) Reorder the terms: -6 + 30z + -5(2 + z) = 11(z + 1) -6 + 30z + (2 * -5 + z * -5) = 11(z + 1) -6 + 30z + (-10 + -5z) = 11(z + 1) Reorder the terms: -6 + -10 + 30z + -5z = 11(z + 1) Combine like terms: -6 + -10 = -16 -16 + 30z + -5z = 11(z + 1) Combine like terms: 30z + -5z = 25z -16 + 25z = 11(z + 1) Reorder the terms: -16 + 25z = 11(1 + z) -16 + 25z = (1 * 11 + z * 11) -16 + 25z = (11 + 11z) Solving -16 + 25z = 11 + 11z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-11z' to each side of the equation. -16 + 25z + -11z = 11 + 11z + -11z Combine like terms: 25z + -11z = 14z -16 + 14z = 11 + 11z + -11z Combine like terms: 11z + -11z = 0 -16 + 14z = 11 + 0 -16 + 14z = 11 Add '16' to each side of the equation. -16 + 16 + 14z = 11 + 16 Combine like terms: -16 + 16 = 0 0 + 14z = 11 + 16 14z = 11 + 16 Combine like terms: 11 + 16 = 27 14z = 27 Divide each side by '14'. z = 1.928571429 Simplifying z = 1.928571429
| 9h=-81 | | 8t+2*t-1= | | X^2+14x-10=0 | | 6x+2*-x-3= | | q(t)=(3t+8) | | 5p-3*2p+4= | | 7r+2*8r= | | y+4*y+3= | | z+7*5z-1= | | (z+7)*(5z-1)= | | 10x-6=6x+14 | | x-5*4=56 | | 6.3=9 | | 3x-9=90 | | 200-3x=33x+24 | | 10-10x=22-17x | | 4(8x-8)=30 | | 4y(y+7)=72 | | 62-2x=8x+2 | | x-3x+10=y+4 | | 6x-18=-96 | | c^2=-15-8c | | 12=6n | | Y=(6x+88) | | 2(3x-7)-4=2(x-3)+12 | | Y=(4x^2) | | -3(-x+7)+5x=-21 | | 6a+17+a-4=41 | | 5y+13=31-4y | | x^2=-.5x-.0625 | | 7x-15=96 | | x^2-26x+120= |